Redescriptions of some Lower Devonian gastropods from Tennessee currently considered to be platyceratids. (16th June 2016) - Harper, John A.
Abstract: Three genera of gastropods described from the Lower Devonian Rockhouse Formation of Hardin County, Tennessee, currently are considered to be junior subjective synonyms of Platyceras ( Visitator ) Perner, 1911. Evaluation of the type specimens of these genera as well as types of two other gastropods from the same formation reveals the following: Platyostoma quadrangulare (Dunbar, 1920) is the only platyceratid gastropod among them; Saffordella tennessensis Dunbar, 1920 has a selenizone above midwhorl so it is an eotomarioidean belonging to the Gosseletinidae; Aulopea nelsoni Dunbar, 1920 and the lectotype of Distemnostoma princeps Dunbar, 1920 each has a broad subsutural sinus on the upper whorl surface similar to the Omphalotrochidae, as well as a basal sinus similar to certain primitive caenogastropods, so their systematic position is uncertain; I consider Holopea planidorsata Dunbar, 1920 to be a juvenile specimen of D. princeps ; the fragmentary paralectotype of D. princeps possibly represents a gerontic form of Distemnostoma curtum Dunbar, 1920, which possesses a well-developed selenizone on an upwardly projecting shoulder at the edge of the upper whorl surface. Because D. curtum appears to be unrelated to D. princeps, the genotype of Distemnostoma, I propose the new generic name Omocordella for D. curtum . The new family Micromphalidae is erected to include Ordovician Slehoferia Rohr and Fryda, 2001, lower Carboniferous Micromphalus Knight, 1945, and Omocordella n. gen.